Nicotine and Cognition in Cognitively Normal Older Adults - Nop, Olivia; Senft Miller, Anna; Culver, Hannah; Makarewicz, Jenna; Dumas, Julie A. (Frontiers in Aging Neuroscience, 2021)
The cholinergic system has been shown to be the primary neurotransmitter system which is responsible for the cognitive symptoms associated with dementia; its role in healthy non-demented older adults remains a gap in the literature. Understanding the effects of age-related functional changes on the nicotinic system will address this knowledge gap. As the older adult population grows and hence the importance of understanding cognitive changes that impact functional abilities and everyday life. In this article we examine the benefits of using nicotine as a method for improving cognition in non-demented healthy older adults which may have the potential for slowing neurodegeneration in aging. Furthermore, we discuss how nicotine can play a crucial role in maintaining cognitive abilities throughout normal cognitive aging.